Relapse after localized rhabdomyosarcoma: Evaluation of the efficacy of second‐line chemotherapy. Issue 11 (6th July 2015) - Winter, Sarah; Fasola, Sylvie; Brisse, Hervé; Mosseri, Véronique; Orbach, Daniel
<x xml:space="preserve">Abstract</x> Purpose About one‐third of patients with rhabdomyosarcoma relapse despite appropriate treatment and experience a poor outcome. Little meaningful improvement in the outcome of this disease has been observed over the last 30 years. There is no clear international recommendation concerning the use of salvage chemotherapy at relapse. A retrospective multicenter analysis was therefore conducted to analyze the efficacy of various second‐line chemotherapy regimens in this setting. Methods Forty‐nine patients under the age of 18, with initially localized rhabdomyosarcoma, who relapsed after first complete remission, treated in three SFCE centers (Société Française des Cancers de l'Enfant) between 1995 and 2013, were analyzed. Results First relapse occurred after a median interval of 22 months and remained localized in 71.4% of cases. All patients received second‐line chemotherapy with an overall response to this salvage therapy of 39.1%. Best specific response rates were 73.3 and 42.9% for carboplatin/epirubicin/vincristine‐ifosfamide/vincristine/etoposide (CEV/IVE) (15 patients) and vincristine/irinotecan ± temozolomide (VI[T]) (seven patients), respectively. Overall, 40 patients (81.6%) were then eligible for delayed local treatment (surgery and/or radiotherapy) and 30 of them (61.2%) achieved second complete remission. After a median follow‐up of 5.4 years since the diagnosis of first relapse, 5‐year overall survival is 49.4% (95% CI: 34.2–64.6). Conclusion Salvage chemotherapy plays a central role in the management of patients with relapsed rhabdomyosarcoma. CEV/IVE and VI(T) regimens can be recommended as neoadjuvant chemotherapy before local treatment for patients with relapsed rhabdomyosarcoma. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.